Interpretation of Modified Electromagnetic Theory and Maxwell's Equations on the Basis of Charge Variation - Asif Ali Laghari (Institute of Advanced Engineering and Science, 2014)
Electromagnetic waves are the analytical solutions of Maxwell's equations that represent one of the most elegant and concise ways to state the fundamentals of electricity and magnetism. From them one can develop most of the working relationships in the electric and magnetic fields. Considering deeply the effect of charge variation in Maxwell’s equations for time varying electric and magnetic fields of charges in moving inertial frame, the magnitude of charge particles vary according to Asif’s equation of charge variation. Consequently the Maxwell’s equations give different results to an observer measuring at rest. This research paper explained the effect of charge variation in Classical Electromagnetic theory, Maxwell’s equations, Coulumb’s law, Lorentz force law when we are referring to any inertial frame.DOI:http://dx.doi.org/10.11591/ijece.v4i2.5351